Cumulative Risk Assessment of Dietary Exposure to Pesticide Residues in Brown Rice (Oryza sativa L.) from the Three Main Rice-Growing Regions in China during 2016–2020. (8th October 2022) - Cao, Zhenzhen; Zheng, Xiaolong; Guan, Meiyan; Zhang, Wanyue; Lin, Xiaoyan; Zhao, Xiaohua; Chen, Mingxue
Abstract : The residual levels of 25 monitored pesticides in 6, 229 brown rice samples obtained from the 17 provinces of the three main rice-growing regions in China during 2016–2020 were analyzed, and the cumulative risks of chronic and acute exposure to pesticides for the Chinese population were assessed. The QuEChERS extraction coupled with liquid chromatography-mass spectrometry for simultaneous determination of 25 pesticide residues in brown rice was developed and validated with good accuracy and precision (recoveries of 70%–120% and RSD ≤20%). The overall detection rate and over the maximum residue limit (MRL) rate of pesticides in brown rice decreased from 39.15% and 3.59% in 2016 to 34.11% and 1.53% in 2020, respectively. The Yangtze River basin had a higher detection rate and over MRL rate (43.14% and 2.88%, respectively) compared with the Southeast Coastal region (37.28% and 2.77%) and the Northeast Plain (11.28% and 0.17%). Isoprothiolane (13.57%) and carbendazim (8.32%) were the most frequently detected in rice samples. Pesticide residues exceeding the MRLs were found most often in triazophos (0.75%) and isocarbophos (0.51%). The risk ranking of pesticide residues based on the ranking matrix showed that carbofuran, methamidophos, and isocarbophos had the highest residual risk scores of 25.09, 25.01, and 25.00, respectively. 17.7% of rice samples contained two or more pesticide residues. The cumulative risk assessments based on the relative potency factor (RPF) approach revealed that the cumulative risks of chronic and acute dietary exposure to organophosphorus, neonicotinoid insecticides, and triazole fungicides from rice ranged from 7.43 × 10 −4 to 3.36 × 10 −2, which were not considered of health concern. The study provides national-scale information on the contamination levels and health risks of pesticide residues in rice, which can help develop continuous monitoring programs for pesticide residue contamination in rice in China.